Cover Image. Issue 7 (13th May 2021) - Zhang, Rui; Guo, Tianwei; Han, Yu; Huang, Hongxin; Shi, Jiamin; Hu, Jiaxuan; Li, Hongjiao; Wang, Jianlin; Saleem, Amina; Zhou, Ping; Lan, Feng
Abstract : The cover image is based on the Review Article Design of synthetic microenvironments to promote the maturation of human pluripotent stem cell derived cardiomyocytes by Rui Zhang et al., https://doi.org/10.1002/jbm.b.34759 .